Nurse Therapeutic Communication Improves Inpatient's Satisfaction - Nur, Kholid Rosyidi Muhammad; Enggal Hadi Kurniyawan; Aditya Bintang Imani; Mutiara Baiq Qatrunnada; Melani Adelia Efendi; Alfid Tri Afandi; Dicky Endrian Kurniawan (International Journal of Midwifery and Health Sciences, 2023)
In nursing practice, communication is a crucial tool to enhance the therapeutic relationship and can affect the quality of nursing services. Therapeutic communication is vital because it can affect patient satisfaction with the medical services. Objective: to explore the relationship between nurse therapeutic communication and inpatient satisfaction. Methods: the method uses a literature review with a prism protocol approach, with ten journals found, five international and five national. The literature search process in this literature review used three databases: Google Scholar, PubMed, and ScienceDirect, with a range of publication years between 2019-2023. The keywords used were therapeutic communication, level of satisfaction, respect, opening up, positive attitude, and inpatient. In the Indonesian literature search, the keywords used were therapeutic communication relationship, level of satisfaction, hospitalization, patient anxiety, therapeutic communication effect, and nurse communication. Results: Nurse therapeutic communication makes inpatients get pleasure. Patient satisfaction can have a good impact on hospitals or health services. The hospital management must carry out supervision related to the implementation of communication in the work program, and all nurses in the hospital must have therapeutic communication skills so that all patients who get treatment at the hospital get satisfaction. Conclusion: various studies have shown a positive relationship between nurses' therapeutic communication and patient satisfaction and motivation. Nurses' attitudes, qualifications, age, and knowledge influence therapeutic communication. Positive character traits can help build strong relationships with patients and increase patient satisfaction.